Association Between the Acute to Chronic Workload Ratio and Injury Occurrence in Young Male Team Soccer Players: A Preliminary Study - Arazi, Hamid; Asadi, Abbas; Khalkhali, Farhood; Boullosa, Daniel; Hackney, Anthony C.; Granacher, Urs; Zouhal, Hassane (Frontiers in Physiology, 2020)
This study aimed to investigate the relationship between the acute to chronic workload ratio (ACWR), based upon participant session rating of perceived exertion (sRPE), using 2 models (1. rolling averages [ACWRRA]; 2. exponentially weighted moving averages [ACWREWMA]) and the injury rate in young male team soccer players aged 17.1±0.7 years during a competitive mesocycle. Twenty-two players were enrolled in this study and performed 4 training sessions per week with 2 days of recovery and 1 match day per week. During each training session and each weekly match, training time and sRPE were recorded. In addition, training impulse (TRIMP), monotony and strain were subsequently calculated. The rate of injury was recorded for each soccer player over a period of 4 weeks (i.e., 28 days) using a daily questionnaire. The results showed that over the course of the study, the number of non-contact injuries was significantly higher than that for contact injuries (2.5 vs. 0.5, p=0.01). There were also significant positive correlations between sRPE and training time (r = 0.411, p = 0.039), ACWRRA (r = 0.47, p = 0.049), and ACWREWMA (r = 0.51, p = 0.038). In addition, small-to-medium correlations were detected between ACWR and non-contact injury occurrence (ACWRRA, r = 0.31, p = 0.05; ACWREWMA, r = 0.53, p = 0.03). Explained variance (r2) for non-contact injury was significantly greater using the ACWREWMA model (ranging between 21-52%) compared with ACWRRA (ranging between 17-39%). In conclusion, the results of this study showed that the ACWREWMA model is more sensitive than ACWRRA to identify non-contact injury occurrence in male team soccer players during a short period in the competitive season.